Ethnic Entrepreneurs (translation by M. Dobryakova) - Waldinger, Roger; AldrichHoward E.; Ward, Robin (Journal of Economic Sociology, 2010)
During recent years there has been a surge of studies of entrepreneurs from different ethnic minorities. Ethnic minoritieshave different resources and face different opportunities than mainstream entrepreneurs.